The influence of mode of delivery on neonatal and maternal short and long-term outcomes - Daniela Siqueira Prado; Rosemar Barbosa Mendes; Rosana Queiroz Gurgel; Ikaro Daniel de Carvalho Barreto; Rosana Cipolotti; Ricardo Queiroz Gurgel (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE: To evaluate the impact of mode of delivery on breastfeeding incentive practices and on neonatal and maternal short and long-term complications. METHODS: A cohort study was conducted between June 2015 and April 2016 with 768 puerperal women from 11 maternities in Sergipe, interviewed in the first 24 hours, 45-60 days and 6-8 months after delivery. Associations between breastfeeding incentive practices, neonatal and maternal, both short-term and late complications, and the exposure variables were evaluated by the relative risk (95%CI) and the Fisher exact test. RESULTS: The C-section newborns had less skin-to-skin contact immediately after delivery (intrapartum C-section: 0.18, 95%CI 0.1-0.31 and elective C-section: 0.36, 95%CI 0.27-0.47) and less breastfeeding within one hour of birth (intrapartum C-section: 0.43, 95%CI 0.29-0.63 and elective C-section: 0.44, 95%CI 0.33-0.59). Newborns from elective C-section were less frequently breastfed in the delivery room 0.42 (95%CI 0.2-0.88) and roomed-in less 0.85 (95%CI 0.77-0.95). Women submitted to intrapartum C-section had greater risk of early complications 1.3 (95%CI 1.04-1.64, p = 0.037) and sexual dysfunction 1.68 (95%CI 1.14-2.48, p = 0.027). The frequency of neonatal complications, urinary incontinence and depression according to the mode of delivery was similar. CONCLUSIONS: The C-section was negatively associated with breastfeeding incentive practices; in addition, C-section after labor increased the risk of early maternal complications and sexual dysfunction.